The Online and Campus (OaC) model as a sustainable blended approach to teaching and learning in higher education: A response to COVID-19 - Rebecca Petronzi; Dominic Petronzi (Journal of Pedagogical Research, 2020)
The COVID-19 pandemic represents an unprecedented challenge for wider society and has impacted all facets of life, including Higher Education Institution (HEIs) provision for teaching and learning - demanding an immediate digital response. The core challenge lies with the inherent choice made by students upon embarking on an undergraduate degree; that face-to-face learning was their preference. Now, HEIs must address this by utilising a range of digital solutions - that crucially, must also be embraced by those that no longer have the luxury to be risk averse or believe that digital solutions align with their existing pedagogical approaches. Higher Education Institutions should be - to an extent - well placed to deliver online provision. This paper aims to explore pertinent literature surrounding blended approaches with regards to key pedagogical and learning theories, with an overall aim of suggesting the Online and Campus (OaC) model as a potential 'blueprint' that incorporates campus, synchronous and asynchronous learning experiences. We refer to asynchronous as flexible, self-paced learning, and synchronous as an environment in which learners are in the same place at a given time (either online or campus) and accessing the same materials. For the purposes of this paper - and the OaC model - both asynchronous and synchronous learning refers to online provision, and we make the distinction between face-to-face teaching by reference to 'Campus'.